Logic and Sets Textbook Containing Ethnomathematics of Sasak Culture: Validation and Design - Sri Subarinah; Junaidi Junaidi; Tabita Wahyu Triutami; Nourma Pramestie Wulandari; Nilza Humaira Salsabila (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
Ethnomathematics in learning mathematics is a trend that needs to be developed, especially in learning that raises local culture. Mathematics and culture have a very close relationship so the development and application of mathematical concepts in the learning process must be based on situations of daily life or local culture. This study aims to develop logic and sets textbooks containing ethnomathematics of Sasak culture. This book is also oriented toward improving higher-order thinking skills. This research is a Research and Development (R&D) by following the ADDIE development model, namely analysis, design, development, implementation, and evaluation. The first year of this research has been carried out until the development phase, namely by developing textbook products according to the design and validating the textbook products. The results showed that the textbook met the 'Very Good' category in the validity test after being assessed by experts so the textbook was suitable to be used as a learning resource.